Answer:
(3, 2)
Step-by-step explanation:
What you do is you take the first problem and move the -2x to the other side with the y to get y+2x=8.
The next thing you do is you substitute the second problem into the y of the first problem like this: (x-1)+2x=8.
The next thing that you do is you add the x's together to get 3x-1=8.
After that, you will add the 1 to both sides to get 3x=9.
The last thing you will do is divide 3 on both sides to get x=3.
How you will solve the y is you take the 3 that you just found out is your x and pug it into the second equation to get y=3-1.
y=2.
(3, 2) is your answer.